Improving dam and reservoir operation rules using stochastic dynamic programming and artificial neural network integration model - Fayaed S.S.; Fiyadh S.S.; Khai W.J.; Ahmed A.N.; Afan H.A.; Ibrahim R.K.; Fai C.M.; Koting S.; Mohd N.S.; Binti Jaafar W.Z.; Hin L.S.; El-Shafie A. (MDPI, 2023)
artificial neural network; dam; integrated approach; model; reservoir; simulation; stochasticity; water relations; water resource